Profil Kemampuan Pemecahan Masalah Siswa SMP Islam Sabilurrosyad pada Materi Persamaan Linear Satu Variabel Berdasarkan Teori APOS DItinjau dari Self-Efficacy - Rahma, Salsabila Zahrani (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
Most students are not able to solve problems well. Although students' math scores are quite good, their ability to solve math problems is actually still lacking. The theory of action, process, object, and scheme functions as one of the theories used to analyze math problem solving based on action, process, object, and scheme. The purpose of This study was to describe the profile of problem-solving abilities of students at Sabilurrosyad Islamic Junior High School on the material of one-variable linear equations based on the theory of action, process, object, and scheme reviewed from the high and low categories of self-efficacy. This study uses a qualitative approach with a case study research type. The subjects of this study consisted of six students representing each high and low self-efficacy category. The data collection techniques used were tests and interviews. The main instrument of this study was the researcher himself who was assisted by other supporting instruments in the form of problem-solving ability test sheets and task-based interview guidelines. The data analysis technique of this study used an interactive model according to Miles and Huberman, namely data reduction, data display, and drawing conclusions. The credibility test of this study used triangulation techniques and increased persistence. The results of the study indicate that, 1) students with high self-efficacy are able to meet all indicators of students' problem-solving abilities in the material of linear equations of one variable based on the theory of action, process, object, and scheme. Students with high self-efficacy solve mathematical problems through the stages of action, process, object, and scheme. However, at the scheme stage they are unable to write conclusions; 2) students with low levels of self-efficacy, although able to pass the stages of the theory of action, process, object, and scheme, show limitations at the stages of object and scheme. At the previous object stage, students were unable to find other objects. Thus, at the scheme stage, students have not been able to connect information from the action, process, object stages correctly. Thus, the following findings indicate that the theory of action, process, object, and scheme can be used as a reference in a more optimal learning and assessment model to improve students' ability to solve mathematical problems. Keywords: Problem Solving Ability, Single Variable Linear Equation System, APOS Theory, Self-Efficacy.